Structural assessment of a population of Anacardium humile subjected to fire during different periods of the year - Sousa,Diego Guimarães de (2020)
ABSTRACT Understanding how fire affects the plant biota of the Cerrado is essential for formulating conservational strategies. We evaluated the effects of fires during different periods of the year on the populational structure of Anacardium humile. The research was carried out in areas of typical cerrado stricto sensu in the territory of the Kalunga, state of Goiás, Brazil. These areas, which comprise the same population, were submitted to the following treatments: unburned (control), burned in May 2016 (early fire - EF), and burned in September 2016 (late fire - LF). In July 2018, we delimited two contiguous transects of 100 x 20 m, subdivided into 10 plots of 20 x 20 m, in each area. Fire stimulated the development of branches from basal regrowth in EF and LF. No differences were found in height and diameter of individuals among LF, EF, and the control area. Individuals of EF had size patterns similar to the control individuals, indicating a lesser effect of early fire. The greatest differences regarding all significant parameters were found between LF and control individuals. Early prescribed fires, depending on periodicity, may be less harmful to A. humile.